SISTEM INFORMASI PENDAFTARAN ONLINE SISWA BERBASIS WEB PADA SEKOLAH MENENGAH KEJURUAN (SMK) PELAYARAN JAKARTA RAYA - Dava Luthfi Alamsyah; Zulhalim Zulhalim; Anton Zulkarnain Sianipar; Ito Riris Immasari (Journal of Information System, Informatics and Computing, 2021)
Online New Student Admission (PPDB) as a method or method that aims to register online for new prospective cadets at SMK Pelayaran Jakarta Raya. With the development of Information Technology (IT) today, information about schools to prospective cadets without being geographically restricted must be conveyed through the website so that the public can easily access all school information. Admission of new cadets at the beginning of a new academic year, in which in practice the admission of new cadets is still done manually so that it cannot be done efficiently. With the existence of a web-based computerized information system, it is hoped that it can help prospective cadets in registering and getting accurate information so they can find out the effectiveness of this system. This writer applies the waterfall design to the building sketch of the information system for new student admissions, the waterfall method is a method that describes the design of the System Development Life Cycle (SDLC), where the preparation begins with analysis, design, coding, and testing. Data collection techniques by conducting field observations, interviews, and literature studies. This new student admission information system was built using the PHP programming language using the MySQL database as the database server. The result of this writing is a web-based student admission information system that has effectiveness in providing convenience to parents of new cadets to receive all information regarding new student admissions and carry out the online registration process.